Examining the effect of managing GHG emissions on business performance. (27th March 2017) - Capece, G; Di Pillo, F; Gastaldi, M; Levialdi, N; Miliacca, M
Abstract: Unprecedented climate changes menace not only the planetary ecosystem, but also the stability of the global economy. The European Union has for years promoted the transition of the economy towards a model of sustainable development, stimulating companies to adopt a strategic approach based on quality and environmental efficiency, rather than on quantity and reduction of costs. The aim of this study is to analyze how greater attention to the environmental effects of a company's activities (environmental management) and monitoring and reduction of CO2 emissions (emission management) can improve the company's economic performance. We analyze the financial data and greenhouse gas (GHG) emission figures for a sample of large Italian companies, searching for potential relations between increasing returns on capital invested and the reduction of pollutants. The results show that the companies examined are ever more attentive to environmental policies, and that those with a green vision achieve better operating performance. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment